Developing Multimodal Literacy in English Grammar Learning through Interactive Digital Media: A Case Study - Asih Puji Lestari; Helmi Hibatullah; Laela Hidayati; Nadia Puspita; Lungguh Halira; Pujiati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
Mastery of grammar constitutes a fundamental foundation in basic English language learning. Nevertheless, many students continue to encounter difficulties in accurately comprehending and applying the Present Tense. This study aims to describe the process of developing multimodal literacy in the instruction of Present Tenses, as well as to analyze the effectiveness and student responses to interactive digital media in English language learning on the topic of Present Tenses. The research was conducted at a senior high school in Bogor City employing a descriptive qualitative approach. The subjects consisted of 38 eleventh-grade students. Data collection was performed using multiple techniques, including participatory observation, semi-structured interviews with two students to obtain their insights, opinions, and experiences regarding the use of interactive digital media during the learning process, and documentation consisting of recordings of learning activities and student works integrating multimodal elements as part of the research data. The findings indicate that the development of multimodal literacy through interactive digital media in present-tense instruction elicited positive responses and proved effective in enhancing students’ understanding of the material